Understanding plant response to nitrogen limitation for the improvement of crop nitrogen use efficiency - Kant, Surya (Journal of experimental botany, 2011)
Development of genetic varieties with improved nitrogen use efficiency (NUE) is essential for sustainable agriculture. Generally, NUE can be divided into two parts. First, assimilation efficiency involves nitrogen (N) uptake and assimilation and second utilization efficiency involves N remobilization. Understanding the mechanisms regulating these processes is crucial for the improvement of NUE in crop plants. One important approach is to develop an understanding of the plant response to different N regimes, especially to N limitation, using various methods including transcription profiling, analysing mutants defective in their normal response to N limitation, and studying plants that show better growth under N-limiting conditions. One can then attempt to improve NUE in crop plants using the knowledge gained from these studies. There are several potential genetic and molecular approaches for the improvement of crop NUE discussed in this review. Increased knowledge of how plants respond to different N levels as well as to other environmental conditions is required to achieve this